The adsorption of acetylene on Ni(110): An experimental and theoretical study - Weinelt, M.; Huber, W.; Zebisch, P.; Steinrück, Hans-Peter; Ulbricht, P.; Birkenheuer, U.; Boettger, J.C.; Rösch, Notker (Journal of Chemical Physics, 1995)
The adsorption of acetylene on Ni(110) was investigated by temperature programmed desorption (TPD), low energy electron diffraction (LEED), angle resolved ultraviolet-photoelectron spectroscopy (ARUPS), and near edge x-ray absorption fine structure (NEXAFS) measurements, as well as by detailed model cluster calculations and slab model band structure calculations. By combining the experimental results and those of the cluster studies an orientation of the molecules is deduced with the C-C axis parallel to the surface and preferentially aligned along the substrate troughs ([110] azimuth) as well as with a highly coordinated adsorption site in the substrate troughs. A detailed analysis of the photoemission spectrum is given. The proposed adsorption geometry is corroborated by band structure calculations for various alternative sites and orientations that are shown to be very sensitive to the azimuthal orientation of the adsorbed molecules. © 1995 American Institute of Physics.